The adolescent child (Journal of Parents and Teachers, 2026)
Gerard Ph. Guasch describes his educational and therapeutic experience with young people in conflict. Through techniques such as 'mirroring' and 'photodrama', they learn to recognise and value themselves. This helps to promote self-esteem, dialogue and overcoming insecurities. The author emphasises the idea that the education of adolescent girls must begin with reconciliation with their bodies, as this is the basis of their identity and emotional balance.
Keywords: Self-awareness, Self-esteem, Adolescence and Therapy.